EMISI GAS FORMALDEHIDA DARI BEBERAPA TINGKAT KETEBALAN KAYU LAPIS - Suwandi Kliwon (Jurnal Penelitian Hasil Hutan, 1988)
In  this paper  the  determination    of  formaldehyde    gas emission   from  plywood  is presented.   Six  samples  were colected  from  several plywood  factories   in Indonesia  two  samples  were made  by  the center   for  Forest  Products  Research and Development   Laboratory  in Bogor.The  results showed  that  the amount   of  formaldehyde   gas emission  from  plywood  varies from  3.080  ppm  (3.6 mm thick) to  9.933 ppm (for 18.0  mm thick)